The dialogue between the worlds of art and science - Armocida, Giuseppe; Gorini, Ilaria (Medicina Historica, 2017)
How to place today medicine in the overall cultural context remains an open debate. The figure of the physician requires scientific knowledge, technical ability, but must be sustained by a sound humanitarian ethos, stressing the aspects related to communication. We should always keep in mind that the physician shall master instruments based on creativity, artistic valence, centered on the individual, rather than methodologically founded procedures, in a comprehensive and holistic frame.